HUBUNGAN KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DENGAN KARAKTER GOTONG ROYONG SISWA KELAS IV di SD NEGERI KEBONSARI 2 MALANG - Azzahro, Sivi Mariska (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
Technological advancements bring both positive and negative impacts on humans. One of the negative impacts is the increasing dependence on gadgets, which leads to a decline in the spirit of mutual cooperation. Therefore, efforts are needed to reduce teenagers' dependence on gadgets, one of which is through the Pancasila Student Profile Strengthening Project with the theme